2022
DOI: 10.1371/journal.pgen.1010079
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of Hsp70 is responsible for paralog-specific regulation of ribonucleotide reductase

Abstract: The Hsp70 family of molecular chaperones is well-conserved and expressed in all organisms. In budding yeast, cells express four highly similar cytosolic Hsp70s Ssa1, 2, 3 and 4 which arose from gene duplication. Ssa1 and 2 are constitutively expressed while Ssa3 and 4 are induced upon heat shock. Recent evidence suggests that despite their amino acid similarity, these Ssas have unique roles in the cell. Here we examine the relative importance of Ssa1-4 in the regulation of the enzyme ribonucleotide reductase (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Several studies have suggested that these chaperone paralogs have overlapping but unique interactomes [ 34 ]. Recently, work using the model substrate ribonucleotide reductase (RNR) showed a clear preference for this client in binding Ssa1 and Ssa2 [ 35 ]. Although Apn2 binds cytosolic Hsp70 and Hsp90 paralogs equally, cells expressing Ssa1 as their sole cytosolic Ssa1 are unable to support WT levels of Ape2 as depicted by compromised stability in Figure 1 B,C.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that these chaperone paralogs have overlapping but unique interactomes [ 34 ]. Recently, work using the model substrate ribonucleotide reductase (RNR) showed a clear preference for this client in binding Ssa1 and Ssa2 [ 35 ]. Although Apn2 binds cytosolic Hsp70 and Hsp90 paralogs equally, cells expressing Ssa1 as their sole cytosolic Ssa1 are unable to support WT levels of Ape2 as depicted by compromised stability in Figure 1 B,C.…”
Section: Discussionmentioning
confidence: 99%